4f-2p-3d orbital overlap in a metal-organic framework-derived CeO2/CeCo-LDH heterostructure promotes water oxidation - Maurya P.; Ansari T.; Indra A. (My University, 2025)
Herein, we have demonstrated a facile method for the synthesis of CeO2/Ce-Co-LDH heterostructures using zeolitic imidazolate framework-67 as the precursor. The Ce-incorporation in Co-LDH results in 4f-2p-3d orbital overlap to tune the electronic structure whereas the oxygen-deficient CeO2 controls the interface charge transfer. This results in excellent water oxidation activity to attain 500 mA cm−2 current density at 320 overpotential. © 2023 The Royal Society of Chemistry.